A German Monograph on Ancient Georgian Inscriptions - Nino Aptsiauri (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
The present article deals with the study by Heinz Fähnrich, a well-known German scholar and Kartvelologist, published by Brill Academic Publishers in 2013, in Germany. The new monograph "Ancient Georgian Inscriptions" (Diealtesten georgische ninschriften) explores the diachronic pattern of Georgian writing though the example of the development of Georgian inscriptions and introduces a new argument emphasizing the tendency of letters to modify their graphic form that is, by acquiring an angular shape. Based on the latter argument the scholar attempts to restore the pattern of the chronological development of the Georgian alphabet. This article discusses fundamental arguments within the monograph and determines their relation to previous academic thought.